2020
DOI: 10.21203/rs.2.22523/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of talent management practices on service delivery of doctors in Nairobi, Kenya: A descriptive research study

Abstract: Background : A reliable and dedicated health workforce is instrumental in the attainment of Universal Health Coverage and Sustainable Development Goal (SDG) three on health. This is even more appropriate for Kenya where there is a dire shortage of health workers, and where health workforce management has been devolved to county governments. This study focusses on the influence of talent management practices (attraction, training and development, and retention) on doctor’s service delivery in four county hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The basis for explaining the hypothesis is drawn from the empirical studies on employee sourcing and talent management. The finding from the study agrees with empirical studies linking organizational effectiveness to employee sourcing (Argue, 2015;Oaya et al, 2017;Rapando & Nzulwa, 2018;Jonah et al, 2019), talent management (Kaleem, 2019;Onuko & Onyango, 2020) and talent retention (Aleck, 2019). The recruitment and selection procedures directly affect service delivery through the effective staffing process, which helps the organization obtain skilled and experienced individuals (Gamage, 2014).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The basis for explaining the hypothesis is drawn from the empirical studies on employee sourcing and talent management. The finding from the study agrees with empirical studies linking organizational effectiveness to employee sourcing (Argue, 2015;Oaya et al, 2017;Rapando & Nzulwa, 2018;Jonah et al, 2019), talent management (Kaleem, 2019;Onuko & Onyango, 2020) and talent retention (Aleck, 2019). The recruitment and selection procedures directly affect service delivery through the effective staffing process, which helps the organization obtain skilled and experienced individuals (Gamage, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Empirical studies on talent management have been varied in several contexts. The study examined several studies in Sub-Saharan Africa (Nkala et al, 2021;Tshukudu, 2021;Aleck, 2019), the Middle East (Almohtaseb et al, 2020;Kaleem, 2019) and Kenya (Rapando & Nzulwa, 2018;Onuko & Onyango, 2020). Other studies have elaborated the recruitment strategies (Okeke-Uzodike & Subban, 2015; Jonah et al, 2019;Amegashie-viglo, 2014) and developmental strategies (Tshukudu, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that a strategy such as mediation during an employment conflict is critical for reaching an amicable solution and preventing job discrimination. Similarly, Lamare and Lipsky [113] used an empirical study to examine the effects of arbitration on discrimination claims. They found that employment discrimination claims differ from arbitration, which is appropriate for resolving antidiscrimination statutes at work.…”
Section: Construction Industrymentioning
confidence: 99%
“…They found that employment discrimination claims differ from arbitration, which is appropriate for resolving antidiscrimination statutes at work. According to Lamare and Lipsky [113], construction leaders must be aware of mitigating employment conflicts based on religion, race, age, or physical disabilities to create e conducive work environment. Employers or small construction business owners may use job embeddedness theory for mediation, arbitration, or direct negotiation in their daily managerial activities to promote employee retention strategies and reduce voluntary employee turnover.…”
Section: Construction Industrymentioning
confidence: 99%